Faktor-Faktor Ekonomi yang Memperngaruhi Pengungkapan Islamic Social Reporting - Jaka Darmawan; Widya Eka Saputri (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
The objective of this research was to examine the factors economic affecting the Islamic social reporting disclosure on the companies indexed in Jakarta Islamic Index. The number of samples used in this research was 15 companies. The sampling technique used in this research was purposive sampling. The data analyzing technique used in this research was through the multiple regression test, the determination test, the F test, and the t-test. The analytical tool used in this research was SPSS version 20. The result of this research that the R-square was 0.622 0r 62,2% which meant that the independent variable (the profitability, the leverage, the liquidation, the company size, the industry type, the public ownership shares, and the company age) were able to affect the dependent variable (the Islamic social reporting) and the remaining variable 37,8% was affected by the other outside this research. Moreover, there was a significant effect between the company size, the industrial type, the public ownership shares, and the company age on the Islamic social reporting disclosure. This study still has limitations, among others, the sample of this study is only companies listed on the Jakarta Islamic Index. Sources of information used in research to examine only limited data on company year reports, financial reports, and sustainability reports. The results of this study are one of the company's information in carrying out social activities and provide insight into the knowledge of the factors that affect the disclosure of Islamic social reporting in the Jakarta Islamic Index.